PENGARUH VARIASI TEGANGAN DAN WAKTU PELAPISAN TERHADAP KEKILAPAN, KEKERASAN DAN KEKASARAN PERMUKAAN ALUMINIUM - Ade Irvan Tauvana (KURVATEK, 2016)
The objectives of this research are to determine the influence the voltage and time variations of nickel plating against braightness, hardness, and surface roughness of aluminum specimen and to determine the optimum conditions of coating, so that the condition was obtained plating process copper, nickel and chromium are the most effective which can produce the highest brightness and hardness. Materials Testing square with a length of 5cm, 5cm wide and 0.5 cm thick. Specimen coated copper (12V, during 5 second), then coated with nickel (1V, 2V, 3V, 4V, during 5,10,15,20,25 minutes) variation of voltage and time in the nickel plating is an independent variable of this research, and then coated with chromium (12V during 5 second). Tests conducted to determine surface brightness, hardness and surface roughness. Brightness test conduct with Luxmeter, hardness test with micro Vickers method with a 10gr load, and surface roughness test with roughness test. Brightness test result shows that specimen (2V,25 minutes) have the highest brightness (78%), and specimen (1V, 5 minutes) have the lowest brigthness(50%). Hardness test results show that the raw material surface have the hardness of is 38.3 VHN, shown at the highest hardness of specimens (2V, 25 minute) = 229 VHN and specimens (3V, 20 minute) = 229 VHN, an increase of 497.9% compared to the basic specimen hardness.